Implementation of a Contact Center with Interactive Voice Response Using Cisco Unified Communications - Setiyanto, Rudi; Sofjan, Moh.; Agam, Oky (Institut Teknologi dan Bisnis Bina Sarana Global, 2024)
A popular voice-based communication service used to receive calls automatically is Interactive Voice Response (IVR). Generally, IVR is widely used by institutions to provide services to the public in consulting, offering, or providing information about a particular matter. One of the uses of IVR, among others, is the Contact Center. By using Voice over Internet Protocol (VoIP) technology and using the SIP Trunk service from the service provider, institutions can take advantage of the existing network infrastructure to save on telephone usage. VoIP technology also allows it to be integrated with Private Automatic Branch Exchange (PABX) using Cisco Unified Communications Manager (CUCM). While the IVR system uses Cisco Unified Contact Center Express (UCCX). In this study, the implemented contact center serves to receive calls from external parties. The telephone number uses a call hunting system that will distribute incoming calls to officers on duty at PT. Multipolar Technology Tbk.